Analisa Pemasangan UPS VFD LFO Feeder Untuk Mengantisipasi Gangguan Eksternal - Pancane, Dikse; Kameswara, Angling; Adrama, Gede (Universitas Pendidikan Nasional, 2021)
On July 1 and July 26 2017 there was a simultaneous trip of PLTDG Units 1,2,5,5,6,7,8 and PLTDG Units 1,3,4,5,6,7,8,9 due to a momentary drop voltage due to disturbance kites on the 150 KV line network sanur – gianyar. From the trip conditions, it shows that there is a problem with the generator unit equipment which causes PLTDG units 1,2,3,4,5,6,7,8,9 to trip due to a momentary drop voltage. From the results of the analysis, it is known that the unit trip was caused by a trip on the Pht Line 150 KV to the ship - Padang sambian on the Padang sambian side which resulted in a drop voltage on the low voltage side of 280.4 V or 29.9%. from Unominal. The trip limit of 200MW low-voltage PLTDG according to technical data is 351V or 12.3% of Unominal. The best option to solve the drop voltage fault solution is to install a 10KVA UPS on the LFO feeder pump power supply. The difference before and after the installation of the UPS feeder LFO is that before the installation of the low voltage UPS it drops to 280.4 V or 29.9% of Unominal, and the machine load drops to 11.6 MW. For the results after UPS installation there is no drop voltage value on the low voltage side which means that the UPS installation is successful as a voltage drop solution. So that the difference is obtained on the low voltage side of 119.6 V and on the engine load of 5 MW. Thus, the implementation of a UPS installation on a 200MW PLTDG is very important, in addition to supporting the reliability of the generator system and speeding up recovery in the event of a drop voltage, it can also be economically profitable, so that the company does not lose when the generating unit trips.